IMPLEMENTASI PENDIDIKAN KARAKTER PADA PEMBELAJARAN SEJARAH KELAS XII DI MADRASAH ALIYAH HIDAYATUS SHIBYAN - Surai, Surai; Khosmas, F. Y.; Chalimi, Ika Rahmatika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
Abstract The purpose of this study is to determine the application of character education in learning history which has a strategic meaning in the formation of Indonesian human character with a sense of nationalism and love for the homeland. This study used a qualitative approach by discussing the results of data processing in the field about the implementation of character education, starting from observations, interviews and realistic results. The implementation of character education in Madrasah Aliyah Hidayatus Shibyan Kubu Raya is adjust to the institutional curriculum reference on the Yellow Book â€˜Alim MutaÃ¡lim which teaches the exemplary of a student with a teacher, so that all teachers can implement character education properly in accordance with the local content reference. Then the history teacher also integrates in every syllabus and RPP in implementing character education in class XII in particular. The character education is adjust to the conditions during the learning process. The implementation of character education experienced several obstacles including time, environment, and electronic media. Keywords: Character Education, History Learning, Implementation